2002
DOI: 10.1074/jbc.m110520200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Binding Multiple Ligands by the Common Cytokine Receptor γ-Chain

Abstract: The common ␥-chain (␥ c ) that functions both in ligand binding and signal transduction is a shared subunit of the multichain receptors for interleukin (IL)-2, IL-4, IL-7, IL-9, IL-15, and IL-21. The structural basis by which the ectodomain of ␥ c contributes to binding six distinct cytokines is only partially defined. In the present study, epitope mapping of antagonistic anti-␥ c monoclonal antibodies led to the identification of Asn-128 of mouse ␥ c that represents another potential contact residue that is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Consistent with this observation, mutational studies of the g c cytokine binding site show that the critical energetic hotspots for different cytokines (e.g. IL-2, -4, -7 and -15) are focused on unique zones of an overlapping binding site, 56 thus minimizing the need for a common, structurally insensitive cross-reactivity mechanism. In contrast, the gp130 binding site is almost completely overlapping, necessitating the need for a large degree of thermodynamic plasticity to accommodate the unique surfaces, which it engages by the identical receptor amino acids.…”
Section: Discussionmentioning
confidence: 65%
“…Consistent with this observation, mutational studies of the g c cytokine binding site show that the critical energetic hotspots for different cytokines (e.g. IL-2, -4, -7 and -15) are focused on unique zones of an overlapping binding site, 56 thus minimizing the need for a common, structurally insensitive cross-reactivity mechanism. In contrast, the gp130 binding site is almost completely overlapping, necessitating the need for a large degree of thermodynamic plasticity to accommodate the unique surfaces, which it engages by the identical receptor amino acids.…”
Section: Discussionmentioning
confidence: 65%
“…The TUGm2 epitope has been predicted to be centered near Lys-158 of m γ c, and the antagonistic effect of 4G3 and TUGm2 in the γ c cytokine signaling pathway has been demonstrated. Thus, previous studies regarding the cytokine cross-linking assay with mutant molecules, the predicted location of these epitopes, and the inhibitory properties of the mAbs suggest that they are the pivotal sites in direct ligand-receptor interactions [35]. In addition to previous reports, we found that γ c surface protein on LNT cells was not detected by immunostaining with 4G3 and TUGm2 mAbs upon IL-7 stimulation, although the expression of γ c was intact upon IL-7 stimulation as proved by the immunostaining with anti- γ c pAbs, indicating that 4G3 and TUGm2 are essential sites of conformational change as well as ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…The α chain is specific to IL-2, while the γ chain is shared among IL-4, IL-7, IL-9, IL-15 and IL-21 [48]. The β chain of the IL-2R is also a component of the IL-15 receptor, in conjunction with a specific IL-15R α chain [49].…”
Section: Discussionmentioning
confidence: 99%